An Appraisal of Production Sustainability of Brinjal - R. P. Chaudhary; Rakesh Pandey; A. K. Chaturvedi; R. Prasad (Journal of Agricultural Extension Management, 2014)
Brinjal is one of the most commonly grown vegetables in India. The cultivation of brinjal generally takes place round the year. This paper evaluates the production system in terms of sustainability. The incremental growth in area and production of brinjal over the last five years indicates that a major change is realized in cultivation of brinjal by harvesting more returns per unit area over per unit cost. The observed sustainability yield index (SYI) of brinjal was 0.88 and it reveals that there is an expansion in area and production of brinjal in the district. Besides, the level of technological gap was also minimized from full gap - partial gap to partial gap - no gap. The use of fertilizers and pesticides were particular environmental concerns associated with the cultivation of brinjal. Therefore, more emphasis should be given in this direction, so that these two most important (INM & 1PM) package of practices may not be ignored in future by majority of the farmers.